2010
DOI: 10.1007/s00381-010-1140-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in adults with spina bifida

Abstract: Introduction-Individuals with neurodevelopmental disorders have been observed to show accelerated cognitive aging or even dementia as early as 30 and 40 years of age. Memory deficits are an important component of age-related cognitive loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…26,37,38,105 Outcome assessments should include traditional neuropsychological assessments as well as interview-based measures of adaptive behavior and rating scales.…”
Section: Theme 4: Outcome In Hydrocephalus Neuropsychological Outcomesmentioning
confidence: 99%
“…26,37,38,105 Outcome assessments should include traditional neuropsychological assessments as well as interview-based measures of adaptive behavior and rating scales.…”
Section: Theme 4: Outcome In Hydrocephalus Neuropsychological Outcomesmentioning
confidence: 99%
“…In young adults with SBM, ranging in age from18 to 36 years, Dennis et al (2007) reported lower performance relative to TD individuals on a composite prospective memory score from the Rivermead Behavioural Memory Test (RBMT; Wilson, Cockburn, & Baddeley, 1985). In the only memory study to date that has included middle-aged adults with SBM (age range 18 to 63 years), Dennis et al (2010) reported poorer time- and event-based prospective memory performance on the Cambridge Prospective Memory Test (Wilson et al, 2005) among adults with SBM relative to TD adults.…”
Section: Memory In Sbmmentioning
confidence: 99%
“…Of particular importance when studying adults with SBM and other neurodevelopmental disorders is the question of accelerated normal or pathological aging (Dennis et al, 2010). Individuals with neurodevelopmental disorders other than SBM have been shown to exhibit more rapid cognitive aging and/or dementia neuropathology as early as 30 to 40 years of age (Devenny, Krinsky-McHale, Sersen, & Silverman, 2000; Hagerman & Hagerman, 2004).…”
Section: Memory In Sbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that along with a variety of sensorimotor and cognitive deficits (Dennis et al, 2010;Simos et al, 2011), specific cognitive operations relying on the interhemispheric integration of function are significantly affected in children with SBH, most prominently in cases where partial agenesis of the corpus callosum is present (Hannay et al, 2008;Klaas et al, 1999). It is likely that compromised interhemispheric effective connectivity is a cause of this loss of function, especially considering the corresponding reduced anatomical connectivity.…”
Section: Introductionmentioning
confidence: 99%